A class of single-stranded telomeric DNA-binding proteins required for Rap1p localization in yeast nuclei. - Konkel, L M (1995)
We have identified a class of proteins that bind single-stranded telomeric DNA and are required for the nuclear organization of telomeres and/or telomere-associated proteins. Rlf6p was identified by its sequence similarity to Gbp1p, a single-stranded telomeric DNA-binding protein from Chlamydomonas reinhardtii. Rlf6p and Gbp1p bind yeast single-stranded G-strand telomeric DNA. Both proteins include at least two RNA recognition motifs, which are found in many proteins that interact with single-stranded nucleic acids. Disruption of RLF6 alters the distribution of repressor/activator protein 1 (Rap1p), a telomere-associated protein. In wild-type yeast cells, Rap1p localizes to a small number of perinuclear spots, while in rlf6 cells Rap1p appears diffuse and nuclear. Interestingly, telomere position effect and telomere length control, which require RAP1, are unaffected by rlf6 mutations, demonstrating that Rap1p localization can be uncoupled from other Rap1p-dependent telomere functions. In addition, expression of Chlamydomonas GBP1 restores perinuclear, punctate Rap1p localization in rlf6 mutant cells. The functional complementation of a fungal gene by an algal gene suggests that Rlf6p and Gbp1p are members of a conserved class of single-stranded telomeric DNA-binding proteins that influence nuclear organization. Furthermore, it demonstrates that, despite their unusual codon bias, C. reinhardtii genes can be efficiently translated in Saccharomyces cerevisiae cells.